HUBUNGAN KERAPATAN MANGROVE TERHADAP LAJU SEDIMEN TRANSPOR DI WILAYAH PESISIR DESA PULAU SEMBILAN KABUPATEN LANGKAT SUMATERA UTARA - Rudi Hasonangan Siregar; Yunasfi Djayus; Ahmad Mutadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Mangrove forests in coastal areas physically serves as a barrier of mud and sediment trap. Mangrove are often utilized by people aquaculture activities by means of mangrove forest logging and timber extraction as building materials and firewood, thereby reducing the catch mangrove roots as sediment traps. The purpose of this study was to determine in fluence of mangrove density on the sediment transfort rate in Coastal Pulau Sembilan Village. The research was conducted for two months from March to April 2014 in Coastal Pulau Sembilan Village. The method used is the method of transects and sediment trap method. The results of this study is the highest density of mangrove are found at statiun 4 with a value of 4930 stands/ha and lowest were in station 5 with a value 3662 stands/ha and categorized good. Relationship between the mangrove density and sedimen transfort rate exhibits a negative correlation with a value of -1 this means that sediment rate will be lower when mangrove density higher and vice versa.Key Word : Mangrove Density, Transect Method, Sediment Traps Method, Sediment .Transfort Rate.